The Influence of Tax Knowledge and Tax Policy on Taxpayer Compliance among SMEs in West Java - jinaan, Lu'luatul; Khoirunnisa , Aulia; Nisrina, Zahra Audhya (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2026)
Purpose – This study aims to examine the influence of tax knowledge, administrative barriers, and tax policy impact on taxpayer compliance among Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia. The study also seeks to provide an integrated behavioural perspective regarding how taxation understanding, administrative conditions, and government policies shape voluntary taxpayer compliance within the self-assessment taxation system. Methods – This study applies a quantitative research design using primary data collected through questionnaires distributed to MSME taxpayers in West Java. The sample consists of 53 MSMEs selected using simple random sampling techniques. Data analysis was conducted using SmartPLS version 4 through Structural Equation Modeling (PLS-SEM), including validity testing, reliability testing, multiple linear regression analysis, and hypothesis testing at a 5% significance level. Findings - The findings demonstrate that tax knowledge and tax policy impact positively and significantly influence MSME taxpayer compliance. Tax policy impact emerges as the strongest predictor of taxpayer compliance. It idicates that supportive, fair, and understandable tax policies strengthen voluntary compliance behaviour among MSMEs. Meanwhile, administrative barriers do not significantly influence taxpayer compliance individually. Simultaneously, tax knowledge, administrative barriers, and tax policy impact significantly affect MSME taxpayer compliance, explaining approximately 74.3% of the variance in taxpayer compliance behaviour. Implications - The study provides practical implications for taxation authorities and local governments to strengthen MSME taxpayer compliance through taxation education, simplified administrative systems, and supportive taxation policies. The findings also highlight the importance of improving taxpayer understanding and designing policies that create perceptions of fairness, accessibility, and institutional support within the taxation system. Originality - This study contributes to taxation and accounting literature by integrating tax knowledge, administrative barriers, and tax policy impact within a behavioural taxation framework to explain MSME taxpayer compliance in a regional post-pandemic context. The study also provides empirical evidence from West Java regarding the simultaneous influence of behavioural, administrative, and policy-related factors on MSME taxpayer compliance under Indonesia’s self-assessment taxation system.